If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + y = 3y + -10 Reorder the terms: x + y = -10 + 3y Solving x + y = -10 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. x + y + -1y = -10 + 3y + -1y Combine like terms: y + -1y = 0 x + 0 = -10 + 3y + -1y x = -10 + 3y + -1y Combine like terms: 3y + -1y = 2y x = -10 + 2y Simplifying x = -10 + 2y
| z^6+iz^3+i-1=0 | | 150=50x | | 195=39x | | 5(x)+5(x+3)=225 | | 3(2x+x)=2700 | | 5a-5+2a-7= | | 2x+x*3=2700 | | x^06=0.75 | | 10*x+6*(0.8-t)=6 | | 2x^2-5x+28=0 | | 6lny=3lne^2-9lnx | | x+y+6+5x+2y=180 | | 15d^-5/5d^-8 | | 5x+2y=3x-6 | | 5x+2(x-20)=380 | | 3x^3+3x^2+4x=16 | | 2x+(x+60)+(3x-30)=180 | | 0.6g+11=-5 | | X/a-1= | | 7.8/7.41 | | 5a+(2a-5)-(a-3)=16 | | 7(4y-9)-(4y+8)= | | b^2-7b-36=0 | | (e-b)(c-d)= | | 21-6x=9 | | -243^(3/5) | | 3y-1+2x-4+x+3+15= | | 8x+46=5(x+5) | | 3n-4l= | | 6x^2=15 | | 6.1x-1.5=10.7 | | 2x+4=12+x |